The Anch'Or Harpoon Technique With a Manually Expandable Stentretriever (Tigertriever 13), a Technical Note - Wang, Maud; Elens, Stephanie; Bonnet, Thomas; Halut, Marin; Suarez, Juan Vazquez; Mine, Benjamin; Lubicz, Boris; Guenego, Adrien (Frontiers in Neurology, 2022)
Background and purpose Stent and balloon anchor techniques have been described to obtain distal support and straighten catheter loops, stabilize microcatheters in giant aneurysms, or access distal tortuous anatomy during thrombectomy. These techniques require catheterization of distal arteries with a microcatheter but tortuosity and length issues may render it challenging, precluding the distal unsheathing of a classical auto-expandable stentretriever with the anchor technique. Methods Therefore, we developed the so-called Anch'Or Harpoon Technique using a manually expandable stent retriever, the Tigertriever 13 (Rapid Medical, Yoqneam, Israel). Here, the stent retriever is not unsheathed but pushed out of a microcatheter, and then advanced as far as possible before manual opening. Results and conclusion This technique may be used in 2 different situations. First, in the case of vessel tortuosity if the microcatheter can't be advanced as far as the physician wants: the Tigertriever 13 could be delivered through the microcatheter without having to unsheathe it, and be advanced and opened distally to its microcatheter to establish a stable anchor prior to advancing the guiding, intermediate, and micro-catheters (Anchor technique). The second situation is when distal occlusions lead to length issues; the microcatheter may be too short to cross a distal clot: the Tigertriever 13 could then be pushed out of the microcatheter, and be used to cross a sub-occlusive clot as it has a soft shaped distal tip and the physician has a visual on the artery beyond the sub-occlusion. Then, the Tigertriever would be manually expanded through the clot and retrieved (Harpoon technique) to obtain a recanalization.